Population pharmacokinetics and dose optimisation of colecalciferol in paediatric patients with chronic kidney disease. Issue 3 (30th September 2021) - Wan, Mandy; Green, Bruce; Iyengar, Arpana Aprameya; Kamath, Nivedita; Reddy, Hamsa V.; Sharma, Jyoti; Singhal, Jyoti; Uthup, Susan; Ekambaram, Sudha; Selvam, Sumithra; Rait, Greta; Shroff, Rukshana; et al.
Abstract : Aims: The prevalence of vitamin D deficiency is high in children with chronic kidney disease (CKD). However, current dosing recommendations are based on limited pharmacokinetic (PK) data. This study aimed to develop a population PK model of colecalciferol that can be used to optimise colecalciferol dosing in this population. Methods: Data from 83 children with CKD were used to develop a population PK model using a nonlinear mixed effects modelling approach. Serum creatinine and type of kidney disease (glomerular vs . nonglomerular disease) were investigated as covariates, and optimal dosing was determined based on achieving and maintaining 25‐hydroxyvitamin D (25(OH)D) concentration of 30–48 ng/mL. Results: The time course of 25(OH)D concentrations was best described by a 1‐compartment model with the addition of a basal concentration parameter to reflect endogenous 25(OH)D production from diet and sun exposure. Colecalciferol showed wide between‐subject variability in its PK, with total body weight scaled allometrically the only covariate included in the model. Model‐based simulations showed that current dosing recommendations for colecalciferol can be optimised using a weight‐based dosing strategy. Conclusion: This is the first study to describe the population PK of colecalciferol in children with CKD. PK model informed dosing is expected to improve the attainment of target 25(OH)D concentrations, while minimising the risk of overdosing.